Malnutrition and anaemia among adult women in India. Issue 5 (September 2019) - Bharati, Susmita; Pal, Manoranjan; Sen, Soumendu; Bharati, Premananda
Abstract: The latest National Family Health Survey conducted in 2015–16 (NFHS-4) showed that malnutrition and anaemia still pose huge health challenges in India. Data on 651, 642 adult non-pregnant women aged 15–49 years were taken from the survey to study the nutritional and anaemia statuses of adult women by Indian zone and state. The relationships of these two variables with the women's urban/rural place of residence, education level, religion and eating habits, and wealth index of the family, were assessed. Body Mass Index (BMI) and haemoglobin level were used to assess nutritional status and level of anaemia, respectively. The results show that in 2015–16 in India the percentages of underweight and obese/overweight people were 22.4% and 18.4%, respectively. The percentages of undernutrition and overnutrition were more or less same. The percentage of underweight people was higher in the middle belt region of India. Zones with high levels of overweight or obesity were concentrated in the West, North and South zones. A comparison of the two national-level data sets, i.e. NFHS-4 and NFHS-3, showed that the prevalences of undernutrition and anaemia reduced by 13 and 5 percentage points, respectively, from NFHS-3 to NFHS 4, i.e. over the 10-year period from 2004–05 to 2015–16, whereas overnutrition increased by 4 percentage points during this period. Analysis of possible socio-demographic factors and eating habits thought to influence underweight, obesity and anaemia revealed substantive causal relations. More specifically, education and eating habit were found to influence underweight, overweight or obesity and anaemia significantly. The nutritional status of a woman was also found to depend on household income.